PENGARUH PENAMBAHAN VIRGIN COCONUT OIL DALAM PENGENCER TRIS KUNING TELUR TERHADAP KUALITAS SPERMATOZOA SAPI BALI SELAMA PRESERVASI (Infiluence addition virgin coconut oil in tris egg yolk on the quality of bali bull spermatozoa during preservation) - Jernih Blegur; Wilmientje M Nalley; Thomas Mata Hine (JURNAL NUKLEUS PETERNAKAN, 2020)
The purpose of this study was to examine the effect of adding various doses of virgin coconut oil to the quality of bali bull spermatozoa during preservation. Semen is accommodated twice a week using an artificial vaginal method from two 3-4 year old bali bull with normal body condition and reproductive organs. Semen with motility> 70%, concentration> 1000 × 106, and abnormality <15% was diluted with Tris-egg yolk (T-KT) diluent added with virgin coconut oil (VCO) at a concentration of: 0% (T0), 2 % (T1), 4% (T2), and 6% (T3). The diluted semen was stored at 3-5ᶱC. Evaluated every 24 hours for motility, viability, abnormalities and vitality of spermatozoa up to a motility of at least 40%. The results showed that semen diluted with T-EY with 6% VCO (T3) had a higher quality (P <0.05) compared to the other three treatments, with motility reaching (43.10 ± 2 , 83%), viability (48.68 ± 1.59%), abnormalities (5.92 ± 0.90%) and survival (6.00 ± 0.00 days). The conclusion of this study is the addition of 6% virgin coconut oil in Tris-egg yolk diluent is more effective in maintaining the quality of bali cattle liquid semen.